Lived Experiences Of Female Learners In South African Grade 12 Physical Sciences Classrooms (Journal of Namibian Studies : History Politics Culture, 2025)
Despite South Africa having achieved gender parity in enrolment numbers for science-related subjects, challenges such as exclusion and lack of support persist, affecting girls' engagement in STEM fields. The aim of this study was to explore the experiences of female learners in South African Grade 12 Physical Sciences classrooms. A qualitative research approach and phenomenological research design were adopted. A total of 12 participants were selected from four schools through purposive sampling. To be eligible, learners had to be at least 18 years old and enrolled in Physical Sciences. Ethical clearance was obtained from Turfloop Ethics Research Committee (TREC). Data was constructed through individual open-ended interviews, observations, and document analysis. Data was analysed using thematic data analysis. Four themes emerged from the data: lack of confidence in learning Physical Sciences, work overload, a lack of role models in STEM in society. and learners’ experience with teachers. This emphasises the need for inclusive teaching strategies, teacher training and mentorship to improve learning and close the gender gap in STEM education.